Application of Synchrotron Radiation-Based Micro-Analysis on Cadmium Yellows in Pablo Picasso's Femme. (October 2022) - Ghirardello, Marta; Gonzalez, Victor; Monico, Letizia; Nevin, Austin; MacLennan, Douglas; Patterson, Catherine Schmidt; Burghammer, Manfred; Réfrégiers, Matthieu; Comelli, Daniela; Cotte, Marine
Abstract: Abstract : The cultural heritage community is increasingly exploring synchrotron radiation (SR) based techniques for the study of art and archaeological objects. When considering heterogeneous and complex micro-samples, such as those from paintings, the combination of different SR X-ray techniques is often exploited to overcome the intrinsic limitations and sensitivity of the single technique. Less frequently, SR X-ray analyses are combined with SR micro-photoluminescence or micro-Fourier Transform Infrared spectroscopy, which provide complementary information on the molecular composition, offering a unique integrated analysis approach. Although the spatial correlation between the maps obtained with different techniques is not straightforward due to the different volumes probed by each method, the combination of the information provides a greater understanding and insight into the paint chemistry. In this work, we discuss the advantages and disadvantages of the combination of X-ray techniques and SR-based photoluminescence through the study of two paint micro-samples taken from Pablo Picasso's Femme (1907). The painting contains two cadmium yellow paints (based on CdS): one relatively intact and one visibly degraded. SR micro-analyses demonstrated that the two Cd-yellow paints differ in terms of structure, chemical composition, and photoluminescence properties. In particular, on the basis of the combination of different SR measurements, we hypothesize that the degraded yellow is based on nanocrystalline CdS with high presence of Cd(OH)Cl. These two characteristics have enhanced the reactivity of the paint and strongly influenced its stability.